(untitled) (Eastern Journal of Medical Sciences, 2017)
Background and Aim: Dexmedetomidine, a congener of clonidine is an ?2 adrenoceptor agonist, commonly used for sedation, alsoknown to have antishivering potential. Its use as an agent to treat and control post-spinal anesthesia shivering has been inadequatelystudied. This study is thus aimed to evaluate the efficacy, hemodynamic changes and side effects of dexmedetomidine in comparisonto tramadol when used to control post-spinal anesthesia shivering. Materials and Methods: A prospective randomized, and doubleblindstudy was conducted in 60 ASA Grade I and II patients of either gender, aged between 18 and 60 years, undergoing varioussurgical procedure under spinal-anesthesia and developing shivering. The patients were randomized into two groups of n = 30each to receive either dexmedetomidine - 0.5 ?g/kg (Group D) or tramadol - 0.5 mg/kg (Group T) as an intravenous infusion onappearance of shivering. The time of onset, grade of shivering, time taken for cessation of shivering, response rate, and adverseeffect were observed at scheduled intervals. SPSS-20 was used for statistical analysis, unpaired t-test for numerical data andchi-square test for categorical data. Results: Both the drugs effectively controlled shivering, taking almost the same time for itscessation. It was observed that patients in Group D were found to have a greater sedation score, whereas the side effects such asnausea and vomiting requiring treatment was more in Group T. The incidence of recurrence of shivering was higher in Group T.Conclusions: Dexmedetomidine effectively controls shivering taking almost the same time for cessation as that of tramadol. Itprovides an additional benefit of intraoperative sedation.